Evaluating music teacher performance through 360-Degree Feedback: A study in a music education institution - Dewi, Amelia Miranti; Satitidjati Dewayana, Triwulandari; Suhardini, Didien (OPSI, 2025)
Yayasan Pendidikan Musik Music School in Jakarta has been operating for years without a performance measurement system for its employees, which makes it difficult to improve service quality and efficiency, as well as the effectiveness of the activities carried out. This study aims to design and implement a performance measurement system for music teachers using the 360-degree feedback method. This method is used to provide an objective and comprehensive assessment of performance. Performance criteria are evaluated through a literature review that is tailored to the duties, responsibilities, and job descriptions of the teachers, and then weighted using Pairwise Comparison. The performance measurement tool is implemented in the evaluation of three teachers, assessed by superiors, colleagues, students or parents, and themselves. The assessment results are then analyzed to identify areas for improvement. The results of this study show that all teachers received an average final score of 4, indicating good performance.